2012
DOI: 10.1186/1477-7827-10-74
|View full text |Cite
|
Sign up to set email alerts
|

Expression of antiapoptosis gene survivin in luteinized ovarian granulosa cells of women undergoing IVF or ICSI and embryo transfer: clinical correlations

Abstract: BackgroundThe purpose of the study was to determine the incidence of survivin gene expression in human granulosa cells during ovarian stimulation in Greek women with normal FSH levels, undergoing IVF or ICSI and to discover any correlation between levels of gene expression and clinical parameters, efficacy of ovulation or outcomes of assisted reproduction.MethodsTwenty nine women underwent ovulation induction for IVF or ICSI and ET with standard GnRH analogue-recombinant FSH protocol. Infertility causes were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…The gene expression levels of survivin in total pregnant patients were higher than those in total non pregnant patients [88]. Moreover, Varras et al (2012) studied only normal women (male factor infertility) and women with tubal factor infertility who underwent IVI or ICSI and embryo transfer [69]. Women with endometriosis or polycystic ovarian syndrome were not included in their study since endometriosis and androgens promote apoptosis [85,89].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The gene expression levels of survivin in total pregnant patients were higher than those in total non pregnant patients [88]. Moreover, Varras et al (2012) studied only normal women (male factor infertility) and women with tubal factor infertility who underwent IVI or ICSI and embryo transfer [69]. Women with endometriosis or polycystic ovarian syndrome were not included in their study since endometriosis and androgens promote apoptosis [85,89].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that survivin might try to protect ovaries, with possible influenced perfusion due to ipsilateral salpingectomy. In cases with tubal inflammation or hydrosalpinges survivin might try to protect the ovaries from follicular apoptosis in a paracrine environment [69]. The authors suggested their hypothesis about the levels of survivin mRNA expression in ovarian granulosa cells in tubal factor infertility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell apoptosis in the case of most apoptosis-inducing signals is known to occur via related protease (Varras et al, 2012). Survivin resists the induction of apoptosis at the G 2 /M stage of the cell cycle through cell cycle-dependent expression.…”
Section: Discussionmentioning
confidence: 99%